2020
DOI: 10.1016/j.triboint.2019.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Debris development in fretting contacts – Debris particles and debris beds

Abstract: Response to reviewers' commentsWe would like to thank the reviewers and the editor for their input on the paper, and for the opportunity to make minor revisions to the text. We appreciate both reviewers' positive comments regarding the overall content of the paper, and have implemented the sole change recommended which is summarised below:We are familiar with the work of Arnaud and Fouvry et al., whose recent work on debris the reviewer has identified as being relevant to the present work. Of the papers we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…However, several studies demonstrated that debris particles formed in steel alloys have a size ranging from 0.01 to 1 µm [17,[42][43][44][45][46] and some others reported a size ranging from 1 to 10 µm [47,48]. By combining the current SEM observations (Fig.…”
Section: Longitudinal Dispersivity ( )supporting
confidence: 54%
“…However, several studies demonstrated that debris particles formed in steel alloys have a size ranging from 0.01 to 1 µm [17,[42][43][44][45][46] and some others reported a size ranging from 1 to 10 µm [47,48]. By combining the current SEM observations (Fig.…”
Section: Longitudinal Dispersivity ( )supporting
confidence: 54%
“…Fretting-induced damage is a widespread problem that manifests itself in a wide range of industrial applications ranging from cables and riveted connections in civil engineering contacts to blade/disk assemblies in aeronautics [3,4]. Many efforts were made during the past decades to investigate how the contact loading conditions such as the normal force, frequency, sliding amplitude, contact size, ambient and temperature conditions could influence fretting wear [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The links between wear (i.e. in this case purely a physical process) and dissipated energy have been clearly shown in the literature for fretting contacts [10,28,[32][33][34]. Similarly, the links to corrosion and its synergies during tribocorrosion have been quantified in recent work for fretting-corrosion contacts in simulated biological environments [35][36][37].…”
Section: Discussionmentioning
confidence: 92%